Penerapan Nilai-nilai Moderasi Beragama di SMP Al-Kenzie - Daila Nur Azizah; Aulia Adline; Luthfi Putra Ramadhan; Aji Setiaji (Pascasarjana IAI Nasional Laa Roiba Bogor, 2025)
Implementing religious moderation values in schools is an effective step to help students implement a culture of tolerance. In Indonesia, where there are so many different cultures and religions, religious moderation is very important, but there are still some obstacles in its implementation. This research aims to see how schools can teach these moderation values, so that schools play a very important role in helping students become more open minded and respectful of each other. This research uses a qualitative approach with a descriptive method. Data collection techniques used observation, interviews and documentation. The results showed that the application of religious moderation values in schools not only strengthens harmony between students, but can also build an attitude of tolerance and respect for differences in society. The obstacles in instilling religious moderation at school, that is: students come from families with various religious backgrounds and views on different religions. Some families may have more exclusive views, while others are more open to differences.